On linear almost periodic pulse systems - Tkachenko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For a linear almost periodic system under pulse influence, the conditions are established under which this system is reducible (by a linear change of variables with a discontinuous almost periodic matrix) to a system without pulses but with a Bohr almost periodic right-hand side. The set of linear almost periodic pulse systems possessing only bounded solutions is studied.